Evaluation of the mitigation potential of the adaptation strategies implemented in the Climate – Smart Villages (CSV) - Loaiza, Sandra; Silva, Mayesse Aparecida da; Chirinda, Ngonidzashe; Martínez Barón, Deissy (2018)
Digital maps of soil loss water erosion in the 2014 and potential the study areas of Popayán - Colombia and Matagalpa - Nicaragua were generated by means of the soil loss equation (USLE / RUSLE), which relates soil properties (percentages of sand, clay, limousines and carbon contents) obtained from secondary information and world map of the world (DSMW), version 3.6 of the FAO (2002), the erosion index of rainfall and runoff with information of the databases of the meteorological stations of the IDEAM and the Nicaraguan Institute of Territorial Studies (INETER) and of the databases of Global Climate Monitor, types of crops / practices of observation and conservation of ECOHABITAS of the year 2014 of the program of Climate – Smart Village (CSV) of Climate Change, Agriculture and Food Security (CCAFS) and topographic conditions from a digital elevation model SRTM of 30 meters resolution.